1995
DOI: 10.1068/p240477
|View full text |Cite
|
Sign up to set email alerts
|

Processing Speed in the Motion-Induction Effect

Abstract: Abstract. The motion-induction effect, where an illusory motion is perceived within a bar when it is shown next to a spot presented slightly earlier, was studied with respect to the idea that it is based on differential processing speeds between the two ends of the bar. First, by using just a bar with a luminance gradient, the existence of a motion illusion (gradient motion) within such a bar was demonstrated, presumably due to the different processing speeds of differential luminances. When such a bar was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…In the current study, however, motion was perceived in the opposite direction, toward the light end of the gradient bar when it replaced the uniform bar, perhaps because motion energy is more readily extracted when the gradient bar is exchanged with a uniform bar compared with presenting it on a blank field. When a square was presented, and an adjacent gradient bar appeared afterward, von Grünau et al's (1995) results were very similar to ours. That is, they found that strong LMI motion was perceived when the square was adjacent to the light side of a gradient bar, but not when it was adjacent to its dark side.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In the current study, however, motion was perceived in the opposite direction, toward the light end of the gradient bar when it replaced the uniform bar, perhaps because motion energy is more readily extracted when the gradient bar is exchanged with a uniform bar compared with presenting it on a blank field. When a square was presented, and an adjacent gradient bar appeared afterward, von Grünau et al's (1995) results were very similar to ours. That is, they found that strong LMI motion was perceived when the square was adjacent to the light side of a gradient bar, but not when it was adjacent to its dark side.…”
Section: Resultssupporting
confidence: 88%
“…A series of experimental conditions similar to those of the current experiment previously was reported by von Grünau, Saikali, and Faubert (1995). When they presented a gradient bar on a blank field, they found by a relatively small margin that the direction of perceived motion was toward the dark end of the gradient 3 .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This is important, because if (as gradient hypotheses suggest) the modulatory effects of a gradient are strongest at its peaks, then presenting the probe line at a distance from the primers is likely to weaken the ability for gradient-modulated signals at the probe location to influence perception. Several investigations have shown that what appears to be a gradient drops off with distance from the primer in a quasi-exponential fashion (Miyauchi, Hikosaka, & Shimojo, 1992; Steinman, Steinman, & Lehmkuhle, 1995; Stelmach & Herdman, 1991; Stelmach et al, 1994; von Grünau, Racette, & Kwas, 1996; von Grünau, Saikali, & Faubert, 1995). Downing and Treisman's (1997) gaps between the primer and the line probe were 208% the size of their primer.…”
Section: Methodsmentioning
confidence: 99%
“…The speed of neural processing is increased by attention, causing sensory data from the line end nearest the cued location to be centrally processed more rapidly (sooner) than data from more remote regions, leading to the percept of sequential line appearance, i.e., motion. That the induced line motion effect is attentional in origin is illustrated by the fact that the illusion can be produced by cue and line stimuli that are perceptually dissimilar in color, luminance and stereo depth (von Grünau, Saikali & Faubert, 1995), and by the ability of both auditory and somatosensory cues to elicit this visual effect (Shimojo, Miyauchi & Hikosaka, 1997). …”
Section: Introductionmentioning
confidence: 99%